1996
DOI: 10.2307/1543060
|View full text |Cite
|
Sign up to set email alerts
|

Particle Capture by the Gills of Dreissena polymorpha: Structure and Function of Latero-frontal Cirri

Abstract: Microscopic techniques were used to examine the role of gill cirri in particle capture by Dreissena polymorpha. The latero-frontal cirri, formed from two fused ciliary plates, consist of about 40 pairs of cilia. Each cilium in the plate contains a typical 9 + 2 axoneme in the fused region of the cirrus, but the structure of the axoneme in the long, free ciliary tips is reduced. The cilia in a cirrus are graded in length, with the shortest cilia positioned frontally. The cirral cilia move in unison, allowing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 45 publications
4
52
0
Order By: Relevance
“…Moreover, Lithophaga appears to use its gill to collect particles via 2 basic mechanisms, mechanical sieving and aerosol trapping, as described in many previous studies (Silverman et al, 1996;Dufour and Beninger, 2001). The ciliated protozoa accommodated in the axial canal of the ctenidia and observed in the present study appear to be an important component of the nutrition and feeding of L. lithophaga.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Moreover, Lithophaga appears to use its gill to collect particles via 2 basic mechanisms, mechanical sieving and aerosol trapping, as described in many previous studies (Silverman et al, 1996;Dufour and Beninger, 2001). The ciliated protozoa accommodated in the axial canal of the ctenidia and observed in the present study appear to be an important component of the nutrition and feeding of L. lithophaga.…”
Section: Discussionsupporting
confidence: 76%
“…The structure of the fused pairs of latero-frontal cilia in L. lithophaga is thought to be effective in water current, particle capture, and transport. This structure has been extensively described as a composite structure of 8-20 fused cilia in certain other bivalve species (Atkins, 1938;Ward et al, 1993;Silverman et al, 1996;David and Fontanetti, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, these two D. polymorpha waste products, being settleable [21], could easily remove from the water column the bounded pollutants (as MEs). Moreover, taking into account the indirect ability of bivalves to bioaccumulate many environmental contaminants, including MEs [22], we can point out the potential of D. polymorpha to this purpose [23][24][25][26]. In this regard, a study conducted in 1983 by Piesik [27] highlighted how D. polymorpha is able to remove nutrients from eutrophic waters and a subsequent research confirmed the potential of D. polymorpha in the reduction of algal density [28].…”
Section: Introductionmentioning
confidence: 90%
“…Ward et al (1998) believed that agreement with the process of direct particle interception, which is found in many other phyla, added robustness to their argument in contrast to many previous explanations which suggested that bivalves had evolved unique processes of particle capture (e.g., Jørgensen 1981). Beninger (2000), Riisgård and Larsen (2000), and Silverman et al (2000) have commented on various aspects of Ward et al (1998). In this paper, we respond to these comments by grouping our responses under common headings that allow us to deal with similar points raised in all three papers.…”
mentioning
confidence: 93%
“…This deceptively easy question has not proven easy to answer mainly because of the difficulties associated with observing capture processes on the ctendial surface of animals enclosed in opaque shells. A variety of hypotheses have been advanced including particle capture by a mucus sheet covering the ctenidia (MacGinitie 1941), physical entrainment by ''sticky'' laterofrontal cilia or cirri that border the filaments of the ctenidia (so called ''lime twig '' model, Wallengren 1905;Tammes and Dral 1955), mechanical sieving of particles from suspension by these same cilia or cirri (Moore 1971;Owen and McCrae 1976;Silverman et al 1996), and entrainment of particles by hydrodynamic mechanisms (Jørgensen 1981;1990). Most of these hypotheses were based on data obtained from surgically altered animals or isolated tissue preparations.…”
mentioning
confidence: 99%